Integration of terrestrial radio and visual radio: A case study of m radio 98.8 Surabaya - Harliantara, Harliantara; Mulyanadi, Deni (Edelweiss Applied Science and Technology, 2024)
In the process of developing transmission technology and internet applications, radio broadcasting institutions are constantly evolving. In an effort to improve management performance, any changes in radio broadcasting technology are always adaptable. This study utilises a qualitative approach that is still rarely used to review the integration of terrestrial and visual radio. Data collection techniques were used through field observations, interviews, and documentation studies. After data collection was completed, data analysis was conducted systematically in three aspects: data reduction, data display, and conclusion drawing. In contrast to the transmission of radio broadcasts over the air or voice broadcasts, this study found that radio broadcasts can also be distributed through audio and video streaming on the internet (also known as the network) in the form of voice, text, images, and video.